Tenesaca Carrillo, G (2024) El derecho a la seguridad ciudadana y el ejercicio de las atribuciones de los servidores policiales en delitos flagrantes. .(Tesis de Pregrado)Universidad Nacional de Chimborazo, Riobamba, Ecuador - Tenesaca Carrillo, Gabriela Estefania (2024)
ABSTRACT: The purpose of this investigation is to determine whether the actions of the National Police of Ecuador in cases of flagrant crimes are aimed at preserving the right to citizen security, understood as the integrated action developed by the State, with the collaboration of citizens. and other public interest organizations, aimed at ensuring coexistence, peaceful development and the eradication of violence. Having as a general objective to analyze the functions and actions of police officers in cases of flagrant crimes in order to determine their impact on the right to citizen security, so methodologically the type of investigation is inductive, legal analytical and legal dogmatic; The type of design is non-experimental documentary, the data collection techniques applied are the interview and the instrument is the questionnaire, the selection of the sample was non-probabilistic, that is, based on the convenience and interest of the researcher, so 4 were selected. professionals, including an expert in citizen security and public order and three specialists knowledgeable in the field of citizen security, police actions and flagrant crimes, resulting in the National Police not fully complying with what is ordered by the Comprehensive Organic Criminal Code in relation to flagrancy, so there would be a violation of the right to citizen security.